1990
DOI: 10.1007/bf00192465
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Clostridium difficile toxin B gene and demonstration of high N-terminal homology between toxin A and B

Abstract: High titered Clostridium sordellii lethal toxin antiserum, cross-reactive with C. difficile cytotoxin B (ToxB), was used to isolate toxB fragments from a C. difficile expression library. Recombinant clones containing toxB fragments of the 5' and 3' end were isolate. A 2.5-kb HincII fragment of chromosomal DNA overlaps both groups of clones. A partial restriction map of the total toxB gene is presented. The gene is positioned upstream of utxA and toxA, toxB has a size of 6.9 kb, corresponding to a 250-kDa polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The two well-characterized CBPs LytA and PspA contain within the C-terminal the repeated signature choline-binding domains that are the distinguishing feature of this family of proteins. As mentioned in the Introduction, these repeated domains have also been found in toxin A (Dove et al, 1990;Wren et al, 1990) and toxin B (Barroso et al, 1990;von Eichel-Streiber et al, 1990) of Clostridia spp. and the glucan-binding proteins and glucosyltransferases of other streptococci (Ferretti et al, 1987;Shiroza et al, 1987;Ueda et al, 1988;Banas et al, 1990;Gilmore et al, 1990).…”
Section: Discussionmentioning
confidence: 79%
“…The two well-characterized CBPs LytA and PspA contain within the C-terminal the repeated signature choline-binding domains that are the distinguishing feature of this family of proteins. As mentioned in the Introduction, these repeated domains have also been found in toxin A (Dove et al, 1990;Wren et al, 1990) and toxin B (Barroso et al, 1990;von Eichel-Streiber et al, 1990) of Clostridia spp. and the glucan-binding proteins and glucosyltransferases of other streptococci (Ferretti et al, 1987;Shiroza et al, 1987;Ueda et al, 1988;Banas et al, 1990;Gilmore et al, 1990).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the similarity in the biochemical activity of TcdA and TcdB, wherein both toxins use a highly conserved N-terminal domain to modify identical substrates, supports the notion of gene duplication. The major regions of homology between TcdA and TcdB fall within the enzymatic and receptor-binding domains of the two toxins (172). The N-terminal domains of TcdA and TcdB show 74% homology, and this homology provides a basis for the similar substrate specificity of these two toxins.…”
Section: Genetics Of Tcda and Tcdbmentioning
confidence: 99%
“…More recently, von Eichel-Streiber et al (281,282) isolated cytotoxin B fragments from a C. difficile expression library by using C. sordellii lethal toxin antiserum. A partial restriction map of recombinant clones showed that the toxB gene is positioned upstream of utxA and toxA and has a size of 6.9 kb corresponding to a polypeptide size of 250 kDa.…”
Section: Introductionmentioning
confidence: 99%